Bladder Tumor in Women with Microscopic Hematuria: An Iranian Experience and a Review of the Literature - Shahin Abbaszadeh; Saeed Taheri; Mohammad Hossein Nourbala (Advances in Urology)
Aim. In this study we report our experience with microhematuria and its relation with bladder tumors in Iranian women. Materials and Methods. Overall 249 women were evaluated. Microscopic hematuria was defined as three or more red blood cells per high-power field on at least two different occasions. Patients with a history of gross hematuria or coagulation disorders, having organic diseases, urinary stones, urinary tract infections, nephrological diseases, and local lesions such as urethral caruncle were excluded from the study population. Final diagnosis of malignant tumors was done with cystoscopy and biopsy specimen pathological assessment in all cases. Results. Age for the study population was 49.7±11.8 years. 95 (38%) of patients were identified during routine check up and presenting symptoms in other patients were frequency, dysuria, stress urge incontinence, urge incontinence, feeling of incomplete urine emptying, and flunk pain, respectively. Finally, 7 (2.8%) of study subjects were confirmed as having bladder tumors. One of tumor cases was diagnosed 24 months after initial assessments. Patients with bladder tumor were significantly older; more frequently had diverticulum in their bladder wall (P<.05). Conclusion. Female microscopic hematuria is relevant and deserves evaluations, especially in elderly patients. Patients whose reason for microhematuria would not be diagnosed at the initial evaluations should be followed.